Another Life (1972), de Derek Walcott, ou les lettres du mal-voyant - Kerry-Jane Wallart (Revue LISA, 2007)
Although it reads as a major poetical text about painting, Another Life unrelentingly pores over such phenomena as disappearance, blindness, visual fallacy or optical distorsions. The paintings that are presented are either out of focus or else steeped in waxing shadows. One may then have to conceive of poetry as superseding painting, as a genre more able to delineate the contours of this invisible world which is so much the concern of our abstract (post)modernity; the poets who are featured as visionary blind men throughout the text might then know how to withdraw from the world in order to better represent it. The purpose of this article is to show to what extent painting is not described by Derek Walcott as a failure but rather as the means of a poetical incarnation through a gesture of diversion from the visible universe. These verses of an unfit seer quickly veer towards a tribute paid to a genre, painting, which is not so much opposed to poetry as made to echo it through graphics which, in Rimbaldian fashion, take on colours.